Textiles and fashion : exploring printed textiles, knitwear, embroidery, menswear and womenswear - Udale, Jenny (Fairchild Books, 2014)
"Textiles and Fashion explores the integration of textile design with fashion. It begins with a brief history of textiles, showing the links with technical innovation and social developments. It then focuses on the processes of textile design, including the ethical and sustainable issues around textiles today. The book also provides practical information on fibre production, dyeing and finishing techniques. Various surface treatments are explored, as well as the way in which colour and trend influences fashion and textiles. Through case studies and interviews, fashion and textile designers discuss their production processes and how they use textiles in their work. New to the second edition are exercises to help students to explore and further their knowledge of textiles and fashion"--Resumé vydavatele
Obsahuje bibliografii (s. 193) a rejstřík
Keywords: textilní design; textilie; módní návrhářství; textile design; textile fabrics; fashion design; příručky; handbooks, manuals, etc